Thrombolysis with alteplase 3–4.5 hours after acute ischaemic stroke: trial reanalysis adjusted for baseline imbalances - Alper, Brian Scott (BMJ Evid Based Med, 2020)
OBJECTIVES: Alteplase is commonly recommended for acute ischaemic stroke within 4.5 hours after stroke onset. The Third European Cooperative Acute Stroke Study (ECASS III) is the only trial reporting statistically significant efficacy for clinical outcomes for alteplase use 3–4.5 hours after stroke onset. However, baseline imbalances in history of prior stroke and stroke severity score may confound this apparent finding of efficacy. We reanalysed the ECASS III trial data adjusting for baseline imbalances to determine the robustness or sensitivity of the efficacy estimates. DESIGN: Reanalysis of randomised placebo-controlled trial. We obtained access to the ECASS III trial data and replicated the previously reported analyses to confirm our understanding of the data. We adjusted for baseline imbalances using multivariable analyses and stratified analyses and performed sensitivity analysis for missing data. SETTING: Emergency care. PARTICIPANTS: 821 adults with acute ischaemic stroke who could be treated 3–4.5 hours after symptom onset. INTERVENTIONS: Intravenous alteplase (0.9 mg/kg of body weight) or placebo. MAIN OUTCOME MEASURES: The original primary efficacy outcome was modified Rankin Scale (mRS) score 0 or 1 (ie, being alive without any disability) and the original secondary efficacy outcome was a global outcome based on a composite of functional end points, both at 90 days. Adjusted analyses were only reported for the primary efficacy outcome and the original study protocol did not specify methods for adjusted analyses. Our adjusted reanalysis included these outcomes, symptom-free status (mRS 0), dependence-free status (mRS 0–2), mortality (mRS 6) and change across the mRS 0–6 spectrum at 90 days; and mortality and symptomatic intracranial haemorrhage at 7 days. RESULTS: We replicated previously reported unadjusted analyses but discovered they were based on a modified interpretation of the National Institutes of Health Stroke Scale (NIHSS) score. The secondary efficacy outcome was no longer significant using the original NIHSS score. Previously reported adjusted analyses could only be replicated with significant effects for the primary efficacy outcome by using statistical approaches not reported in the trial protocol or statistical analysis plan. In analyses adjusting for baseline imbalances, all efficacy outcomes were not significant, but increases in symptomatic intracranial haemorrhage remained significant. CONCLUSIONS: Reanalysis of the ECASS III trial data with multiple approaches adjusting for baseline imbalances does not support any significant benefits and continues to support harms for the use of alteplase 3–4.5 hours after stroke onset. Clinicians, patients and policymakers should reconsider interpretations and decisions regarding management of acute ischaemic stroke that were based on ECASS III results. TRIAL REGISTRATION NUMBER: NCT00153036.